The ICAReB Platform: A Human Biobank for the Institut Pasteur and Beyond. (24th March 2020) - Esterre, Philippe; Ait-Saadi, Amina; Arowas, Laurence; Chaouche, Sophie; Corre-Catelin, Nicole; Fanaud, Christine; Laude, Hélène; Mellon, Vesna; Monceaux, Valérie; Morizot, Gloria; Najjar, Imène; Ottone, Catherine; et al.
The ICAReB platform of Institut Pasteur provides access to human bio-resources for academic and private research teams worldwide, essentially in the fields of infection, immunity and neurosciences. More than 134, 000 human quality controlled, duly annotated samples (mainly whole-blood derived products, but also stool, urine, saliva, swabs….), from both healthy and diseased cohorts with open, regulated access, are available upon request. Both clinical investigation and biobanking activities are certified following ISO 9001:2015 and NF S96-900:2011 standards, respectively. ICAReB is a member of PIBnet (Pasteur International Biobanking network), BIOBANQUES and BBMRI, the French and pan-european biobanking networks, respectively.